159 victim of fate or choice: a study of Greene’s The Heart of the matter - Sresha Yadav,; Smita J, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The present paper aims to find out the possible justification to the question, why an honest and incorruptible police officer like Henry Scobie in the novel The Heart of the Matter indulges in a chain of criminal activities. Paradoxically, this is not the story of Henry Scobie’s life, but the story of every common man, who one or the other day in his life, indulges in such type of activities which are tagged by society as ‘anti-social acts’ or ‘criminal acts’. But the question remains the same, why? This question is the ultimate question for a perpetrator to answer. His mind dwells with the dilemma that whether I was chosen by fate or it was my own choice. Greene’s protagonist, Henry Scobie is like every common man, whose life was entangled with unexpected complexities and miseries. Let’s find out whether it was Scobie’s fate or his choice. The prime objective of the present paper is to find the hidden answer to the question with regard to Greene’s protagonist Henry Scobie’s life. To attain the proposed objective the present study relies upon textual analysis and draws upon the relevant criminological theories like Agnew’s General Strain Theory and Rational Choice Theory.